A Study on Public Complaint in Construction of East Coast Rail Link (ECRL) Project in Section 5 - Nik Husni, Nik Nur Ain Amsyar; Muhamad Faiz Abd Latif; Eady Hafiz Abdul Razak; Abdullah Mohd Nasir (Progress in Engineering Application and Technology, 2024)
The ECRL project, spanning Kelantan, Terengganu, Pahang, and Selangor, involves significant community engagement, particularly from those directly affected and those who have sacrificed their land for construction. Numerous public complaints and concerns have emerged regarding the development of Section 5 of the ECRL project. The proximity of several alignment sites to residential areas has significantly affected and angered the residents. The objectives of this study are to identify the public complaints encountered, propose mitigation plans to prevent their recurrence during the project’s completion, and monitor the effectiveness of the mitigation plan. This study comprehensively examines the issues and public complaints from 2018 to 2023 within Section 5 of the East Coast Rail Link (ECRL) project, choose a mitigation plan that has been used, and identify the verification of the plan to ensure efficient project completion and prevent future issues. The MRL uses SharePoint with a dedicated ’Public Complaint’ section for Section 5 to facilitate communication among staff. Mitigation plans for Section 5 include using water browsers for dust control, culvert improvement for water pollution prevention, rescheduling work to reduce noise, rectifying roads, and deepening trenches to improve drainage and mitigate flooding. The frequency of each issue calculated and one of them which is repeated issue chosen based on all the data of public complaint. The effectiveness of the mitigation plan is monitored on site and determined in the grievance form. The results included a thorough collection of site photos taken before, during, and after the implementation of the actions, along with the maintenance schedule for the mitigation plan and the monitoring of the plan. By determining and monitoring the effectiveness of the applied mitigation plans, it ensures the ECRL project proceeds with minimal disruption to local communities, enhancing overall public satisfaction and safety.